A Cholesterol Recognition Motif in Human Phospholipid Scramblase 1 - Posada, Itziar M.D. (The Biophysical Society, 2014)
Human phospholipid scramblase 1 (SCR) catalyzes phospholipid transmembrane (flip-flop) motion. This protein is assumed to bind the membrane hydrophobic core through a transmembrane domain (TMD) as well as via covalently bound palmitoyl residues. Here, we explore the possible interaction of the SCR TMD with cholesterol by using a variety of experimental and computational biophysical approaches. Our findings indicate that SCR contains an amino acid segment at the C-terminal region that shows a remarkable affinity for cholesterol, although it lacks the CRAC sequence. Other 3-OH sterols, but not steroids lacking the 3-OH group, also bind this region of the protein. The newly identified cholesterol-binding region is located partly at the C-terminal portion of the TMD and partly in the first amino acid residues in the SCR C-terminal extracellular coil. This finding could be related to the previously described affinity of SCR for cholesterol-rich domains in membranes.